Degradation of ornithine transcarbamylase in sporulating Bacillus subtilis cells. - Neway, J O (1983)
When Bacillus subtilis cells grew and sporulated on glucose-nutrient broth, ornithine transcarbamylase (OTCase) was synthesized in the early stationary phase and then inactivated. The loss of OTCase activity was much slower in a mutant that was deficient in a major intracellular serine protease (ISP). Immunochemical analysis showed that synthesis of OTCase decreased to a low, but detectable, level during its inactivation and that loss of activity was paralleled by loss of cross-reactive protein. Because the antibodies were capable of detecting denatured and fragmented forms of OTCase, we conclude that inactivation involved or was rapidly followed by degradation in vivo. Native OTCase was not degraded in crude extracts or when purified ISP and OTCase were incubated together under a variety of conditions. Synthesis of OTCase was not shut off normally in the ISP-deficient mutant. When the effects of continued synthesis were minimized, OTCase was degraded only slightly slower in the mutant than in its parent. Thus, the mutant had unanticipated pleiotropic characteristics, and it was unlikely that ISP played a major role in the degradation of OTCase in vivo.